The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12665-013-2516-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the correlations between freeze–thaw and salt crystallization tests

Abstract: Two of the most popular weathering tests used for dimension stone are EN 12371 freeze-thaw (FT) and EN 12370 Salt Crystallization (SC). These tests are used to assign a durability value to the rocks. Both tests are based on the cyclical growth of crystals in the porous system of the rock, which causes structural stress on the rock matrix that may affect its integrity. The weathering mechanism is the same in both tests although the rate of volume increase is higher for the salt crystals. Due to this similarity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…This pore range was considered as one of the most sensitive ones in terms of salt damage (Yu and Oguchi 2010), while Benavente et al (2004) suggested that larger pores (0.1-10 μm) all contribute to salt damage. Other authors (Steiger 2005a(Steiger , 2005bCárdenes et al 2013) clearly noted that smaller pores can be also considered in salt damage. Frost damage is also linked to porosity, and there is a strong link between humidity, capillary condensation, and frost damage of porous materials (Al-Omari et al 2015;Scrivano et al 2018).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This pore range was considered as one of the most sensitive ones in terms of salt damage (Yu and Oguchi 2010), while Benavente et al (2004) suggested that larger pores (0.1-10 μm) all contribute to salt damage. Other authors (Steiger 2005a(Steiger , 2005bCárdenes et al 2013) clearly noted that smaller pores can be also considered in salt damage. Frost damage is also linked to porosity, and there is a strong link between humidity, capillary condensation, and frost damage of porous materials (Al-Omari et al 2015;Scrivano et al 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The weathering mechanism of porous materials is almost the same in the case of frost and salt crystallization. Some of the salt tests could cause higher structural stress on the stone matrix than frost damage-what suggests, that weathering process is faster in a salt-rich environment (Cárdenes et al 2013). Stone and mortar damage depends on relative humidity (RH), temperature, and pore structure in salt-rich environment (Linnow 2007), while in region, the damage is mainly controlled by the presence of the water, the porosity, the pore size distribution, and the saturation rate (Ruedrich et al 2011, Al-Omari et al 2015, Gökçe et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and duration of FT cycles and the temperature sequence and range applied in those studies varied widely. The concomitant inconsistencies in the findings (Cárdenes, 2014) must be borne in mind when comparing the results.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…During crystallization, some salts are able develop pressures that exceed the tensile strength of the material, increasing the size of the pores by formation of micro-cracks and thereby making the material more porous and more prone to new alteration processes. These pressures are usually higher than the freeze-thaw pressures [14].The deterioration due to presence of soluble salts is associated with the periodic changes in their state,…”
Section: Introductionmentioning
confidence: 99%